Integrated supplier management system a case study: PARL Bone Mills - Rahman Bias, Tanvi (2007)
Effective supplier management is vital for successful business operation of any business organization. Supplier management is a technique and continuous activity that used to control and make decision about supplier management. Cooperative managers make wise supplier management decision by using supplier management strategy as part of an organized plan. Therefore the research is to implement IS in supplier management at PARL Bone Mills. The Management Information System (MIS) will propose a decision making process for the management at PARL Bone Mills. From the initial findings, the management often faces some problems in taking the supplier record where it is done manually. Therefore, the proposed MIS system will be able to choose a useful supplier who will make available of right product as per the organization’s need. By implementing ICT strategy successfully at PARL Bone Mills, especially MIS system, it is hoped that it can bring some effective and efficient improvement to their supplier management system and this project will also help them to reduce their misuse of time.